Percepção dos profissionais da atenção primária à saúde sobre a educação permanente em tuberculose - Grignet, Rodrigo Juliano (2017)
The National Policy on Permanent Education in Health, Administrative Rule n. 198 / 2004 and Administrative Rule n. 1996 / 2007, is a strategy of the Unified Health System for the training and improvement of workers for the sector. It brings in its scope the change in the conception and improvement practices of Unified Health System health workers. In this context, the objective of this study was to verify how the professionals with higher education working in the health area exercising their activities in Primary Health Care in the city of Foz do Iguaçu, Paraná, perceive the Permanent Education in Health as a vehicle of promotion and qualification of care, and their discernment on this theme, when they are exposed to possible models of permanent education, as the knowledge of distance education tools as a cofactor for the improvement of care for patients with tuberculosis attended at Open Units and Family Health Strategy. This is a descriptive epidemiological study of the type inquiry, which adopted as strategy the application of an evaluation instrument of the degree of agreement and disagreement appropriating the Likert Scale, with the participation of APS-linked servers that have or have already had in their routine involvement With patients with tuberculosis. The ethical aspects followed Resolution 466/2012 of the National Health Council. The health units of the municipal network of Foz do Iguaçu-Paraná were constituted as verification units. Data collection was performed between july and september 2016 through a self-administered instrument with 84 health professionals (doctors, nurses, dentists, nutritionists, pharmacists, social workers, others). Quantitative data from the questionnaires were stored in an Excel® database, and statistical analyzes were performed using XLSTAT® software. In order to achieve independence among the questions of the questionnaire and each variable evaluated, the Chi-square test was performed, and in cases where the theoretical score was less than 5 respondents, and the independence of these data could not be attested, The Monte Carlo Method was used. In the questionnaire, 18 assertions were approached in which professionals answered their degree of agreement or disagreement for each exposed statement. The assertions of this study were organized and linked to the three main objectives and to four relations of interest: Sanitary Districts and their mode of attention; Top-level professionals working in the APS and its training area; Time of activity of these in Unified Health System, and the total activity time in health. Assay and quantification of the assertions resulted in 12 tables that showed by the direction of the statistical data a dispersion on the perception of the indicators with the Permanent Education in Health. This condition is considered as the result of poor understanding or perception about what Permanent Education in Health is, its modalities and technological tools that allow the permanent exercise of this one. This results in inadequate insight into the role of health professionals in their appropriation of a collective of thought, and therefore can not have a substantial participation in the resolution of neglected diseases in the case of this study, tuberculosis.